Experimental study on the performance of an array of vertical flexible porous membrane type breakwater under regular waves. (15th November 2022) - Guo, Y.C.; Mohapatra, S.C.; Guedes Soares, C.
Abstract: Experimental investigation on the wave reflection, transmission, and wave energy dissipation of a vertical flexible porous multi-membrane type breakwater is conducted under regular waves. Tests are carried out for a wide range of wave periods, wave heights, membrane porosities, membrane spacing settings, and a different number of membranes. The present results of reflection and transmission coefficients are compared with numerical and experimental datasets available in the literature. Further, the performance of the present vertical flexible porous membrane type breakwater is analyzed by comparing different arrangements of vertical membranes via different wave quantities. The results of the present study can be useful to optimize the design of a vertical flexible porous multi-membrane type breakwater for coastal protection schemes. Highlights: Experiments on the wave reflection, transmission, and wave energy dissipation of a vertical multi-membrane are performed. The results of reflection and transmission coefficients are compared with numerical and experimental data in the literature. The performance of the present breakwater is analyzed by comparing different arrangements of vertical membranes.